How is soil carbon stock in old-growth boreal forests affected by management? - Dahl, Jenny (SLU/Dept. of Forest Ecology and Management, 2018)
Boreal forests are able to store large amounts of carbon in soil and biomass, and forest management is considered an important strategy for mitigating climate change. Sweden has a long history of forest management that have intensified during the last century, but there are still old-growth forests that have not been disturbed by management. These forests have accumulated carbon in the soil during a long time. Since this carbon stock is large, even small changes can affect carbon dioxide levels in the atmosphere. Therefore, it is important to know how soil carbon is affected by management. The aim of this study was to investigate how a change in land use from old-growth forest with long tree cover continuity to young, managed forest affects the soil carbon stock. This was done by quantifying carbon stock in soil and tree biomass in 15 sites of adjacent old and younger forest in Västerbotten and Norrbotten in northern Sweden. The results shows a reduction of total soil carbon stock in managed forests. The reduction was mainly driven by a decrease in humus layer carbon stock, causing an 11 % decrease in total soil carbon stock. It is likely that this was caused by disturbance of the humus layer during harvesting and site preparation, and lack of litter fall during the clear cut period. Mineral soil carbon stock was not significantly affected by management, indicating that above ground operations have little effect on deeper soil layers. These results are in line with earlier studies. It has previously been proved that soil carbon has slow turnover and long term modelling studies predict a decline in soil carbon after several rotations. This study focuses on a short time perspective and the results can be different with a longer time frame perspective. Sammanfattning Boreala skogar kan lagra stora mängder kol i mark och biomassa, vilket gör skog och skogsskötsel till en viktig del i arbetet för att minska klimatförändringar. Sverige har en lång historia av skogsbruk, vilket har intensifierats under det senaste ...